Parametric studies on the behaviour of FRP-strengthened RC wall subject to near-field blast effects and fragment loading and development of fast running model (FRM) - Fung, Tat Ching (Nanyang Technological University, 2020)
Based on the high-fidelity physics based models (HFPBMs) described in report D3, mass runs have been carried out for parametric studies to investigate the influence of material properties and structural parameters on the behaviour of FRP-strengthened RC walls subject to near-field blast effects and fragment loading. Following this, the results obtained from the mass runs have been analyzed using artificial neural network (ANN) methods to develop FRM (Fast running model). Based on the FRM, analysis tools have been developed and preliminary design guidelines are being proposed.